“Hidden” and Diverse Long-Term Impacts of Exposure to War and Violence - Drožđek, Boris; Rodenburg, Jan; Moyene-Jansen, Agnes (Frontiers in Psychiatry, 2020)
Nowadays, the PTSD diagnosis is often a prerequisite for the survivor’s access to specialized treatment services and for obtaining legal recognition or financial compensation when exposed to violence. However, some survivors do not meet all necessary criteria for the PTSD diagnosis, particularly not in the long term. Therefore, they run the risk of being misdiagnosed, inadequately helped or undertreated, and may remain legally unrecognized and unprotected. In this article the “hidden” long-term impacts of exposure to war and violence, beyond the PTSD diagnosis, are presented, discussed, and illustrated with case presentations. They include dissociative states, attachment problems, personality changes, guilt, shame, rage, identity issues, moral injury, damaged core beliefs, and bodily sensations linked to stress activation. These phenomena are not persistent, but fluctuate over the survivor’s life trajectories. Moreover, the “hidden” impacts are framed within theoretical models for understanding long-term impacts of exposure to violence. The models help us grasp the dynamics of interactions between resilience, psychological damage, context and time. These interactions are non linear, and contingently result in development of psychopathological phenomena when reaching a threshold during a process of accumulating potentially traumatic experiences over a survivors’ lifetime. Understanding psychological impacts of exposure to violence as a spectrum of interchangeable phenomena over a lifetime, and learning to recognize the “hidden” manifestations of psychological trauma will help to improve mental and legal assistance to the survivors both on a short and long term.